Detection of cation-specific conformational changes in ribosomal RNA by gel electrophoresis - Morris, David R. (1974)
Electrophoresis of ribosomal RNA in polyacrylamide-agarose composite gels separates 16S and 23S species into multiple bands. These bands of RNA represent multiple conformational forms of the molecules as judged by oligonucleotide analysis of the 16S RNA. Gel electrophoresis was used to test for cation-specific conformational changes in ribosomal RNA. Relative to magnesium-equilibrated RNA, barium ion and putrescine induced alterations in the electrophoretic behavior of ribosomal RNA while calcium ion produced no change. Exchange of a critical level of bound magnesium ion for barium or putrescine was necessary for these changes to take place. The alterations in electrophoretic behavior were unaffected by simply restoring magnesium ion, but in addition required heating for reversal. We suggest that these conformational changes are a result of interaction at a specific class of cation binding sites previously observed with intact ribosomes.